מעורבות - אדורנו, תיאודור (מכאן, 2008)
A Hebrew translation of Adorno's Essay — "Engagement" (1962). AnEnglish translation of the essay can also be found in Notes to Literature,vol. 1, Shierry Weber Nicholsen (trans.). New York: Columbia UniversityPress, 1992, pp. 76-94.